Chapter 5: Kaitiakitanga: Land, People and Resource Management - Kawharu, Merata (Te kōparapara: an introduction to the Māori world, 2018)
Keywords: environment; history; kaitiakitanga; resource management; social conditions; social life and customs

Taking into account the principles of the Treaty of Waitangi: ideas for the implementation of Section 8, Resource Management Act 1991 - Crengle, Diane (Ministry for the Environment, 1993)
Keywords: citizenship; environment; law; management; natural resources; resource management; resource management act 1991; tiriti o waitangi/treaty of waitangi

Environmental and spatial planning with ngā Atua kaitiaki: A mātauranga Māori framework - Walker, Dean P.; Ataria, James M.; Hughey, Kenneth F. D.; Park, Patrick T.; Katene, John P. (New Zealand Geographer, 2021)
Internationally, Eurocentric hegemonies rooted in coloniality dominate the discourse on environmental wellbeing and sustainable development. Māori frameworks are being used and developed in Aotearoa New Zealand to support bicultural approaches to the management of natural resources and built environments. This paper reports on an Atua (Māori gods and spirits) framework that was found to be valuable as a cultural lens for the co-creation of a toolkit for assessing the wellbeing of indigenous forests. This article provides guidance on the development and application of kaupapa Māori frameworks, particularly Atua frameworks, in wider geographical contexts including urban design and spatial planning.
Keywords: bicultural; kaupapa māori; resource management; sustainable development

Chapter 10: Feast or Famine: Customary Fisheries Management in a Contemporary Tribal Society - Tuuta, Evelyn (Waitangi Revisited, 2005)
Keywords: crown policy; environment; government relations; history; kaitiakitanga; land tenure; māori rights; race relations; rangatiratanga; resource management; tiriti o waitangi/treaty of waitangi

Indigenous Peoples’ Energy Projects - Bargh, Maria (2010)
There are increasing numbers of Māori in New Zealand and Aboriginal peoples in Canada involved in the energy sector. In this paper I explore a number of the factors which have been instrumental in Indigenous peoples becoming involved in energy projects. Utilising a ‘weak theory’ approach I provide narratives of three case studies from New Zealand and Canada (Tuaropaki Trust, Hupacasath First Nation, Peavine Métis Settlement). These cases involve renewable and non-renewable energy types – categories which are often used to judge the value of energy projects. I suggest that while these distinctions provide useful analyses, I ask what might happen if we extend the analysis further to consider how the apparent ‘negatives’ and ‘positives’ of each might be being balanced by other activities that the Indigenous companies are involved with.
Keywords: environment; land governance; land ownership; māori trusts; non-renewable energy; renewable energy; resource management; self-determination; tino rangatiratanga

Reflections: Land is Never Just Land - Bargh, Maria; Weavers, Lydia (Women Talking Politics 2019, 2019)
Keywords: land; resource management; te ao Māori

Indigenous Māori values and perspectives to inform freshwater management in Aotearoa-New Zealand - Harmsworth, Garth; Awatere, Shaun; Robb, Mahuru (Ecology and Society, 2016)
In response to widespread water quality and quantity issues, the New Zealand Government has recently embarked on a number of comprehensive freshwater management reforms, developing a raft of national discussion and policy documents such as "Freshwater Reform 2013 and Beyond" and a National Policy Statement for freshwater management (NPS-FM 2014). Recent resource management reforms and amendments (RMA 2014), based on previous overarching resource management legislation (RMA 1991), set out a new approach and pathway to manage freshwater nationwide. Internationally, there is an increasing trend to engage with indigenous communities for research and collaboration, including indigenous groups as active participants in resource management decision making. What is driving this change toward more engagement and collaboration with indigenous communities is different for each country, and we document the progress and innovation made in this area in New Zealand. The indigenous rights of Māori in New Zealand are stated in the 1840 Treaty of Waitangi and in many forms of New Zealand's legislation. Local and central governments are eager to include local indigenous Māori groups (iwi/hapū) in freshwater management planning processes through meaningful engagement and collaboration. Key to the success of collaborative planning processes for Māori are enduring relationships between local government and Māori, along with adequate resourcing for all partners contributing to the collaborative process. A large number of shared governance and management models for natural resource management have emerged in New Zealand over the past 20 years, and some recent examples are reviewed. We provide some discussion to improve understanding and use of the terms used in these management models such as cogovernance, comanagement, and coplanning, and describe some of the more important frameworks and tools being developed with Māori groups (e.g., iwi/hapū), to strengthen Māori capacity in freshwater management and to support good collaborative process and planning.
Keywords: co-governance; environment; hapū; iwi; kāwanatanga; local government; mātauranga māori; resource management; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; water management